TIONGHOA INDONESIA: Dari Dikotomi Ke Mono-Identitas? - Ibrahim Ibrahim (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2013)
The most commonly used by various elements in defining Tionghoa identity is by dividing it into main dichotomy, i.e. totok and peranakan. Nevertheless, totok and peranakan definition themselves have limits that keep continuously debated. Totok is generally understood from the side of its birth and Tionghoa Puritanism, while peranakan is comprehended as identity that mixes each other with locality. As the time goes by, totok and peranakan dichotomy are not relevant anymore. Recent politic development has led to Tionghoa identity option measured singly by the level of more liquid flexibility.